Impact of Digital Content Marketing on Tourist Visit Interest to Melasti Beach: The Mediating Role of Social Word of Mouth - Ida Ayu Kusuma Dewi; Putu Gde Arie Yudhistira; Ni Ketut Wiwiek Agustina (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: This study aims to determine the role of social word of mouth in mediating the influence of digital content marketing on visiting interests. Design/Methods/Approach: This research uses a purposive sampling technique on 385 respondents who used social media and had never visited Melasti Beach tourist attractions. The data collection technique uses a questionnaire. This research uses SmartPLS 4 to test the validity, reliability, and various tests. Findings: As a result of the study, it is found that digital content marketing has a positive effect on visiting interest, digital content marketing has a positive effect on social word of mouth, social word of mouth has a positive effect on visiting interest, and social word of mouth mediates digital content marketing on visiting interest. Originality: The development of digitalization has led to new ways for tourists to look for references through social word of mouth on social media. This research topic becomes very important for marketers considering that the application of content marketing strategies presents social word of mouth on social media. This is important, especially for a tourist attraction, to generate interest in visiting. Practical/Policy implication: Identification of social word of mouth on social media can be used as a benchmark in mediating digital content marketing and visiting interest. The results of this study have implications for the tourist attraction of Melasti Beach to create interesting content.